Coping with the Challenges of Retirement through Appropriate Preparation Strategies - C. U., Sonye; Minaseichinbo, Bamson (Journal of Home Economics Research, 2024)
This paper examines the concept of retirement in Nigeria. It focuses on the need for preparation for retirement, obstacles to the preparations retirement and ways of overcoming these obstacles. The paper concludes that prospective retirees should start planning for retirement from enrolment and it should be geared towards providing for old age. It therefore recommends that prospective retirees should be given appropriate counselling.